Características produtivas e morfológicas do capim Tanzânia em diferentes intensidades de pastejo - Barbero, Rondineli Pavezzi [UNESP]; Barbosa, Marco Aurelio Alves de Freitas [UNESP]; Castro, Leticia Maria de; Ribeiro, Edson Luis de Azambuja [UNESP]; Mizubuti, Ivone Yurika [UNESP]; Bumbieris Junior, Valter Harry [UNESP]; Silva, Leandro das Dores Ferreira da [UNESP] (Univ Estadual Londrina, 2014)
The objective of this study was to determine the best height of the Tanzania grass under grazing, assessing morphological and productive characteristics of the sward. This experiment was conducted in Cidade Gaucha, Parana, where he was rated the accumulation rate and morphological characteristics of Tanzania grass pastures grazed at 20, 40, 60 and 80 cm grazing under continuous stocking with variable stocking rate for beef cattle. The experimental area was 12 hectare divided in paddocks of one hectare each. For each paddock were allocated two grazing exclusion cage for estimating herbage accumulation, and eight samples were taken every 28 days throughout the year 2010. The completely randomized design. The herbage mass of the morphological structures showed a linear positive function of sward heights. The height of defoliation did not influence the rate of herbage accumulation for any of the morphological structures: green leaf, stem + sheaths and senescent material. There were also no differences in leaf: stem ratio. All heights within the range studied provided adequate number of green leaves per tiller. Tanzania grass pastures grazed under continuous stocking between 40 and 60 cm, for providing a good association between accumulation and mass of green leaf blades, and acceptable values of the mass of stem + sheaths and senescent material. Pasture of Tanzania grass under 60 and 80 cm allow of leaves satisfactory accumulation in the autumn.
Production and morphological characteristics of Tanzania grass under different grazing heights
Keywords: Culm; leaf; senescent material; tiller